Variability of Gravity Wave Effects on the Zonal Mean Circulation and Migrating Terdiurnal Tide as Studied With the Middle and Upper Atmosphere Model (MUAM2019) Using a Nonlinear Gravity Wave Scheme - Lilienthal, Friederike; Yiğit, Erdal; Samtleben, Nadja; Jacobi, Christoph (Frontiers in Astronomy and Space Sciences, 2020)
Implementing a nonlinear whole atmosphere gravity wave (GW) parameterization into the Middle and Upper Atmosphere Model, which extend to the lower thermosphere ($160$\,km), we study the response of the atmosphere in terms of the circulation patterns, temperature distribution, and migrating terdiurnal solar tide activity to the upward propagating small-scale internal GWs originating in the lower atmosphere. We perform three test simulations for the Northern Hemisphere winter conditions in order to assess the effects of variations in the initial GW spectrum on the dynamics of the mesosphere and lower thermosphere. We find that the overall strength of the source level momentum flux has a relatively small impact on the zonal mean dynamics. The tails of the GW source level spectrum, however, are crucial for the lower thermosphere dynamics. With respect to the terdiurnal tide, we find a strong dependence of tidal amplitude on the induced GW drag, generally being larger when GW drag is increased.